Determination of the total neutron cross section using average energy shift method for filtered neutron beam - О. О. Gritzay; А. K. Grymalo; V. A. Pshenychnyi (Ядерна фізика та енергетика)
Development of the technique for determination of the total neutron cross sections from the measurements of sample transmission by filtered neutrons, scattered on hydrogen is described. One of the methods of the transmission determination TH52Cr from the measurements of 52Cr sample, using average energy shift method for filtered neutron beam is presented. Using two methods of the experimental data processing, one of which is presented in this paper (another in [1]), there is presented a set of transmissions, obtained for different samples and for different measurement angles. Two methods are fundamentally different; therefore, we can consider the obtained processing results, using these methods as independent. In future, obtained set of transmissions is planned to be used for determination of the parameters E0, Гn and R/ of the resonance 52Cr at the energy of 50 keV.